Suture Stabilization of Open Physeal Fractures of the Great Toe Distal Phalanx (Seymour Fracture). Issue 1 (January 2021) - Reid, Daniel B.C.; Deckey, David G.; Procaccini, Michaela; Eberson, Craig P.
Abstract : Background: Open physeal fractures of the distal phalanx of the hallux are analogous to Seymour fractures of the hand. When missed, these injuries can result in long-term sequelae including infection, pain, nail deformity, and physeal arrest. Nevertheless, there is a paucity in the literature regarding optimal surgical treatment for these challenging injuries. We present a novel technique and case series for suture-only stabilization of Seymour fractures of the great toe. Methods: Billing records were used to identify all children aged 18 years or younger who underwent operative treatment open distal phalanx fracture of the hallux with an associated nail bed injury. Electronic medical records and plain imaging were reviewed to identify mechanism of injury, surgical technique, results, complications, and follow-up. Results: Five boys with a mean age of 10.3 years (range, 5 to 13 y) met inclusion criteria. Forty percent (2/5) of injuries were missed by the initial treating providers. Only 2 patients presented to our institution primarily; 60% (3/5) patients were transferred from other facilities. The mechanism of injury was variable but generally involved "stubbing" the toe. The mean time from injury to surgical treatment was 2.6 days (range, 0 to 6 d). Median follow-up was 2 months (range, 1 to 96 mo). No patient complications (including infection) or reoperations were reported. On follow-up imaging, no physeal bars were evident on patients treated with suture-only technique. Conclusions: Seymour fracture of the hallux are uncommon, and there is frequently a delay in both presentation and diagnosis. Providers should have increased suspicion for these injuries when a physeal fracture of the great toe is associated with bleeding or nail bed injury. Currently, no consensus exists for treatment of these injuries. Suture-only stabilization represents a simple, reliable alternative to pin fixation. Level of Evidence: Level IV—retrospective case series. Abstract : Supplemental Digital Content is available in the text.